‘I can hear the wind and feel it touch me on the nose’: The search for agency of the environment in the dialogue between human and nature. The case of Austin, TX - Kotus, Jacek (Hungarian Geographical Bulletin, 2024)
This study explores specific relationships between humans and nature and seeks an extended ‘social construction of nature’ in the direction of place agency. The research assumes that place can be in agented action and a reciprocal relationship with human and non-human beings. The study’s main aim is to identify whether, from the perspective of contemporary city users, a partnership with the biotic and geographical environment is possible both within and outside the city. From this aim arises a research question: Does an inhabitant of a large city realize the possibility of a dialogue involving an ‘exchange of meanings’ between two entities of interaction that are often highly different (human and non-human beings)? The research uses a questionnaire survey (to recognize general quantitative opinion) and in-depth interviews with selected respondents (to look for deeper explanations). Results show that some urban respondents can see some environmental elements (in and out of the city) as agents and can describe the relationship human-environment in case of a reciprocal action called dialogue.